Essentials of Clinical Anatomy of the Equine Locomotor System - Denoix, Jean-Marie. (Boca Raton, FL : CRC Press, 2019)
Key features: Important features of regional and topographical anatomy are presented using full-color photos of detailed dissections Anatomy is presented in a clinical context Preparations of cross-sectional anatomy facilitate interpretation of diagnostic imaging, such as ultrasonography, MRI images and CT scans All dissections are of fresh material, rather than preserved specimens, to demonstrate the appearance of tissues in the living animal, or at post mortem autopsy Essentials of Clinical Anatomy of the Equine Locomotor System presents a unique photographic record of dissections showing the topographical anatomy of the locomotor system of the horse. Readers of this book will be able to see the position and relationships of the bones, joints, muscles, nerves and blood vessels that make up each region of the forelimb, vertebral column and hindlimb. This new atlas is essential for anybody involved in detailed anatomical study, complex lameness evaluation or advanced imaging techniques in horses. It will be a useful guide for veterinary students, and a reference for equine vets in practice.
L.4 Cross-sectionSChapter M: THE TARSUS; M.1 Physical aspect; M.2 Radiographic anatomy; M.3 Dissected specimen; M.4 Cross-sections; Chapter N: THE METATARSUS; N.1 PHYSICAL ASPECT; N.2 RADIOGRAPHIC ANATOMY; N.3 DISSECTED SPECIMEN; N.4 CROSS-SECTIONS; Chapter O: THE DIGITAL AREA OF THE PELVIC LIMB; O.1 Physical aspect; O.2 Radiographic anatomy; O.3 Dissected specimen; O.4 Cross-sections; Index
OCLC-licensed vendor bibliographic record.
Keywords: Horses -- Anatomy; TECHNOLOGY & ENGINEERING / Agriculture / Animal Husbandry; MEDICAL / Veterinary Medicine / Food Animal